The genus Taraxacum (Asteraceae) in the flora of Ukraine: a revised checklist with special reference to microspecies diversity in the Right-Bank Forest-Steppe (CHORNOMORSKI BOTANICAL JOURNAL, 2026)
Question: What is the current taxonomic composition of the genus Taraxacum in the flora of Ukraine, and how is its microspecies diversity manifested in the Right-Bank Forest-Steppe? Location: Right-Bank Forest-Steppe, with a case study in the south-western part of Kyiv, Ukraine. Methods: The study combined a critical revision of published sources and selected herbarium specimens with targeted, population-based field surveys conducted in April–May 2020 in urban habitats of south-western Kyiv. These data were supplemented by additional irregular observations across the Right-Bank Forest-Steppe. Within local sampling plots (1 m²), 5–7 individuals per population were examined during flowering. Identification was based on com-parative morphological assessment. Nomenclature: Taraxacum – POWO 2026, WFO 2026. Results: The review confirms that Taraxacum in Ukraine remains a taxonomically difficult and inconsistently interpreted genus at the micro-species level. A critical checklist compiled from the literature and the author’s data includes 111 native species and one nothospecies belonging to 17 sections; several additional taxa require confirmation or further study, while T. obliquum and T. officinale s. str. are excluded from the Ukrainian flora on chorological and taxonomic grounds. In the southern part of Kyiv, seven microspecies from the sections Borea, Erythrosperma, and Taraxacum were documented; in the traditional broad concept, they corre-spond to two aggregate species (T. officinale aggr. and T. erythrospermum aggr.). The study revealed pronounced spatial-ecological differentiation: red-fruited xero-phytic taxa of section Erythrosperma were confined to dry slopes and sandy sub-strates of the Kyiv Hills, whereas the representatives of sections Borea and Taraxacum were more evenly distributed across mesic and disturbed urban habi-tats. Comparison of Eastern and Central European taxonomic concepts demon-strated that records previously reported as T. proximum sensu Tzvelev from the lowland part of Ukraine correspond to T. erythrospermum s. str. and T. parnassicum, and that the presence of T. proximum in Ukraine requires confir-mation. Based on supplementary observations, at least 14 species from seven sections are currently documented for the Right-Bank Forest-Steppe, but the regional inventory remains incomplete. Conclusions: The genus Taraxacum in the flora of Ukraine remains taxonomically complex and insufficiently inventoried at the microspecies level. In south-western Kyiv, seven species from three sections were recorded, showing clear spatial and ecological differentiation. Modern concepts of sect. Erythrosperma refined its composition in the Right-Bank Forest-Steppe.
Keywords: biodiversity, native plants, flora, new localities, Middle Dnipro region